"Harry, You Must Stop Living in the Past:" Names as Acts of Recall in John Updike's Rabbit Angstrom. (30th July 2020) - Backhaus, Peter
Abstract : This paper studies the function of names as a stylistic device in literary fiction. The data are taken from John Updike's Rabbit series, which depicts the life of US American Everyman Harry "Rabbit" Angstrom from the late 1950s to the 1980s. Special focus is on Harry's peculiar habit of calling people and places by names that are no longer up to date: former nicknames, maiden names, names of shops that have gone out of business. It is argued that, in so doing, Harry is recurrently invoking memories of his own past. Updike's use of names here reinforces, on an onomastic level, one of the major motifs of the novel: the protagonist's infatuation with a former version of himself.